Pflege: Partnerschaft mit Ärzten auf Augenhöhe = Nursing : partnership with the medical profession on equal terms - Farrenkopf, Ingrid; Fritzmann, Johannes; Mahler, Cornelia; Müller, Gisela (Der Chirurg, 2012)
Partnership on equal terms between the nursing and medical profession at the Surgical Department of the University Hospital Heidelberg has become evident as shown exemplarily in central patient management, wound management and acute pain service. By using the skills of both professions, aims to improve patient care and operational procedures have been agreed. The transfer of competencies and responsibilities needed to achieve these aims has led to an increase in recognition of the nursing profession. Physicians have experienced a clear relief in pressure and quality has simultaneously been improved. This partnership leads to an atmosphere of respect and recognition.
Paralleltitel von Frontdoor übernommen
Gesehen am 29.10.2018